Tolerance of triazole-based fungicides by biocontrol agents used to control Fusarium head blight in wheat in Argentina - Palazzini, Juan Manuel (2018)
Fusarium head blight (FHB) caused by Fusarium graminearum species complex is a devastating disease that causes extensive yield and quality losses to wheat around the world. Fungicide application and breeding for resistance are among the most important tools to counteract FHB. Biological control is an additional tool that can be used as part of an integrated management of FHB. Bacillus velezensisRC 218, Brevibacillus sp. RC 263 and Streptomyces sp. RC 87B were selected by their potential to control FHB and deoxynivalenol production. The aim of this work was to test the tolerance of these biocontrol agents to triazole-based fungicides such as prothioconazole, tebuconazole and metconazole. Bacterial growth was evaluated in Petri dishes using the spread plating technique containing the different fungicides. Bacillus velezensisRC 218 and Streptomyces sp. RC 87B showed better tolerance to fungicides than Brevibacillus sp. RC 263. Complete growth inhibition was observed at concentrations of 20 μg ml−1 for metconazole, 40 μg ml−1 for tebuconazole and 80 μg ml−1 for prothioconazole. The results obtained indicate the possibility of using these biocontrol agents in combination with fungicides as part of an integrated management to control FHB of wheat. Significance and Impact of the Study: This study evaluates the possibility to use biocontrol agents (Bacillus velezensisRC 218, Brevibacillus sp. RC 263 and Streptomyces sp. RC 87B) in combination with triazole-based fungicides to control Fusarium head blight in wheat. The evaluation of biocontrol agents′ growth under in vitro conditions was carried out in Petri dishes containing either prothioconazole, tebuconazole or metconazole. Viability studies demonstrated that B. velezensisRC 218 and Streptomyces sp. RC 87B were more tolerant to the fungicides evaluated. Results obtained reflect the possibility to use fungicides at low doses combined with biocontrol agents.